Phylogeny of the species of Ciconia (Aves, Ciconiidae) based on cranial osteological characteristics - Santos, Suely Silva; Nobushige, Stella Yasmin Lima; Ribeiro, Arthur Serejo Neves; Santos, Francisco das Chagas Vieira; Donatelli, Reginaldo José; Ferreira, Guilherme José Bolzani de Campos; Guzzi, Anderson (Comunicata Scientiae, 2019)
The Family Ciconiidae currently comprises 19 species distributed primarily in the tropical and sub-tropical regions around the world. Recent studies on phylogeny within the genus and families of birds provided a new opportunity for the analysis of the cranial structure in a phylogenetical context. Consequently, the aim was to describe in detail the cranial osteology of the representative species of Ciconia (C. abdimii, C. ciconia, C. episcopus, C. maguari and C. nigra), aiming to compare the characters found amongst the species that form this genus and these with the one from other members of the Family Ciconiidae and determine the family relationships amongst the species, using the methodology of phylogenetic systematic. Cranial osteology has proven to be a good tool for the cladistic analysis of the genus Ciconia, providing osteologic characters that proves the monophyly of the group. The topology of the tree obtained in the present study has revealed itself as well resolved, presenting positive perspectives to the morphologic studies of the genus. The cladogram presented corroborates the hypothesis of the monophyletic characteristic of the Ciconia, the C. ciconia being the most basal of the genus. The topology of the cladogram is: (C. ciconia ((C. nigra (C. abdimii C. episcopus)) C. maguari)). In general, Ciconia presents a specialized skull, with peculiar characteristics and different from what is observed in other groups of birds.